Pomiar i dekompozycja efektywności zysku za pomocą metody DEA - Prędki, Artur (Measuring and Decomposition of the Benefit Efficency with the Help of the DEA Method, 2007)
In the article some propositions of measuring benefit efficiency with the help of the DEA method are considered. Advantages and disadvantages of these measures are pointed, too. Besides, basic properties of these measures are indicated and graphical illustration is made. In the end, the empirical exemplary application of the ones is presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 220-231